The federal deposit insurance fund that didn't put a bite on U.S. taxpayers - Kane, Edward J.; Hendershott, Robert (Journal of Banking & Finance, 1996)
Unlike the Federal Savings and Loan Insurance Corporation and the Bank Insurance Fund, the National Credit Union Share Insurance Fund (NCUSIF) survived the 1980s without falling into a state of accounting insolvency. This paper analyzes how differences in incentive structure constrain the attractiveness of interest-rate speculation and other risk-taking opportunities to managers and regulators of credit unions. Despite these better incentives, robust present-value calculations establish that NCUSIF fell into economic insolvency during the mid-1980s. Besides calculating the extent of this insolvency, the paper also seeks to explain why, after NCUSIF became insolvent, it could rebuild its reserves without an explicit or implicit taxpayer bailout. Our explanation turns on cross-industry coinsurance responsibilities and the shallowness of the fund's observed insolvency relative to industry net worth. We identify forces in the decisionmaking environment tending to limit the depth and duration of unresolved insolvencies at individual credit unions. Managerial opportunities to benefit personally from taking risks that would flow through to NCUSIF are constrained by difficulties in converting a credit union to stockholder form and by the intensity of proactive monitoring of troubled credit unions by sister institutions and other private coinsurers. We conjecture that expanded use of coinsurance and private monitoring could reduce taxpayer loss exposure elsewhere in government deposit insurance systems.